Comparative characterisation of non-monodisperse gold nanoparticle populations by X-ray scattering and electron microscopy. Issue 22 (28th May 2020) - Yang, Ye; Liao, Suiyang; Luo, Zhi; Qi, Runzhang; Mac Fhionnlaoich, Niamh; Stellacci, Francesco; Guldin, Stefan
Abstract : A cross-method comparison for quasi-monodisperse, polydisperse and bimodal gold nanoparticles of 2–7 nm in diameter between conventional image analysis of transmission electron micrographs and small-angle X-ray scattering with form-free Monte Carlo fitting. Abstract : Accurate nanoparticle size determination is essential across various research domains, with many functionalities in nanoscience and biomedical research being size-dependent. Although electron microscopy is capable of resolving a single particle down to the sub-nm scale, the reliable representation of entire populations is plagued by challenges in providing statistical significance, suboptimal preparation procedures and operator bias. While alternative techniques exist that provide ensemble information in solution, their implementation is generally challenging for non-monodisperse populations. Herein, we explore the use of small-angle X-ray scattering in combination with form-free Monte Carlo fitting of scattering profiles as an alternative to conventional electron microscopy imaging in providing access to any type of core size distribution. We report on a cross-method comparison for quasi-monodisperse, polydisperse and bimodal gold nanoparticles of 2–7 nm in diameter and discuss advantages and limitations of both techniques.